A silent invader: disseminated tuberculosis presenting with hepatic abscesses in early childhood - Reddy, Keerthana; Mazumder, Mithila Das; Chimata, Divyasree; Reddy , Vindya (International Journal of Contemporary Pediatrics, 2026)
Disseminated tuberculosis (TB) is a severe and potentially fatal form of Mycobacterium tuberculosis infection caused by haematogenous spread to two or more non-contiguous organs. Diagnosis is often challenging due to its non-specific clinical presentation and resemblance to other systemic infections. We describe a 9-month-old partially immunized male infant presenting with recurrent vomiting, fever, and poor feeding. Imaging revealed hepatic abscesses and pulmonary nodules. Cerebrospinal fluid GeneXpert detected Mycobacterium tuberculosis. The child was managed with first-line antitubercular therapy, supportive care, and nutritional rehabilitation, with marked clinical improvement. Disseminated tuberculosis in infancy is uncommon but carries high morbidity and mortality. Early clinical suspicion, prompt diagnosis, and timely initiation of therapy are crucial for favourable outcomes.